Regional Mechanisms and Intra-State Conflicts: Implementing the African Union’s Principle of Non-Indifference? - Akech, Migai (Strathmore Law Journal, 2020)
The member states of the Organisation of African Unity (OAU) established the African Union (AU) in 2001, following recognition that Africa needed a more effective institution that could maintain peace and security. In particular,the 1994 genocide in Rwanda demonstrated to the continent that it needed to enhance its ability to act before conflicts became unmanageable and destructive.The AU consequently established an institutional framework for the prevention, management, and resolution of conflicts. This institutional framework consistsof two parallel frameworks, namely the African Peace and Security Architecture (APSA).